Experimental investigation of 16 square meter Scheffler concentrator system and its performance assessments for various regions of India. (May 2019) - Kumar, S.; Yadav, V.; Sahoo, U.; Singh, S.K.
Highlights: Experimental Investigation of a 16 m 2 Scheffler technology is carried out. Improvement of optical efficiency using selective coating and grade mirrors. Performance mapping of the system for four regions of India. Effect of heat loss factors on the thermal efficiency of system. Abstract: An experimental investigation of 16 square meter Scheffler concentrator system with automatic polar axis tracking has been carried out. Various test sequences were performed under quasi-steady-state to analyze various parameters like optical efficiency and thermal characteristics of the system. The paper mainly focuses on the experimental analysis of 16 square meter Scheffler concentrator system and its performance assessment for various regions of India such as New Delhi, Leh-Ladhak, Madurai, and Mumbai. It is studied that, the optical efficiency of the system is achieved up to 59% and the convection heat losses (W/m 2 K), radiation heat losses coefficient (W/m 2 K 2 ) are 2.2 and 0.001 respectively. The performance of the system was also studied based on various reflectivity (i.e. 84% and 95%) of the solar-grade mirror and various selective coating (i.e. Silicon based high-temperature coating and black paint). The performance characteristic of the system is also investigated on a seasonal basis i.e. equinox, winter and summer solstice.